HIRARC-Based Occupational Health and Safety Risk Assessment of Sludge Oil Utilization as an Alternative Fuel in the Cement Industry - Intan Suci Wulandari; Dwi Nowo Martono; Haruki Agustina (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Using sludge oil as an alternative fuel promotes circular economy practices by reducing waste and fossil fuel use, while requiring systematic evaluation and control of occupational health and safety (OHS) risks. Objective: This study aims to evaluate OHS risks associated with sludge oil utilization as an alternative fuel in the cement industry using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) framework. Methods: This quantitative study was conducted at PT Solusi Bangun Indonesia Tbk, Cilacap Plant, in February 2026. Data were collected through field observations, structured questionnaires, and company documents from 20 purposively selected respondents involved in sludge oil management. Risk levels were assessed using the HIRARC methodology. Results: A total of 28 potential hazards were identified across five operational stages: waste reception, temporary storage, pre-treatment, kiln utilization, and waste handling and emissions control. The identified hazards were predominantly chemical and physical in nature. Risk assessment results indicated that 21 risks were classified as very high, 4 as high, and 3 as medium. The most critical risks included transportation accidents, fires in buffer vessels, equipment-related injuries, explosions, and fires in the kiln area. These elevated risk levels were driven by the interaction between the flammable properties of sludge oil, suboptimal equipment conditions, workplace environmental factors, and limitations in existing control measures. Current risk controls were largely administrative and reliant on personal protective equipment (PPE), with limited implementation of engineering controls and hazard elimination strategies. Conclusion: Strengthening engineering and systemic controls is essential to ensure safe, effective, and sustainable sludge oil utilization in the cement industry.